The Bcl-2 Homology-3 Domain (BH3)-Only Proteins, Bid, DP5/Hrk, and BNip3L, Are Upregulated in Reactive Astrocytes of End-Stage Mutant SOD1 Mouse Spinal Cord - Duval, Nathan; Sumner, Whitney A.; Andrianakos, Anna G.; Gray, Josie J.; Bouchard, Ron J.; Wilkins, Heather M.; Linseman, Daniel A. (Frontiers in Cellular Neuroscience, 2018)
The molecular mechanisms leading to motor neuron death in amyotrophic lateral sclerosis (ALS) are unknown; however, several studies have provided evidence of a central role for intrinsic apoptosis. Bcl-2 homology-3 domain (BH3)-only proteins are pro-apoptotic members of the Bcl-2 family whose enhanced expression acts as a trigger for the intrinsic apoptotic cascade. Here, we compared the relative expression of BH3-only proteins in the spinal cord of end-stage G93A mutant SOD1 mice to age-matched wild-type (WT) mice. Large alpha motor neurons in lumbar spinal cord sections of both WT and end-stage mutant SOD1 mice stained positively for a number of BH3-only proteins; however, no discernible differences were observed in either the relative intensity of staining or number of BH3-immunoreactive motor neurons between WT and mutant SOD1 mice. On the other hand, we observed significantly enhanced staining for Bid, DP5/Hrk, and BNip3L in GFAP-positive astrocytes only in end-stage G93A mutant SOD1 spinal cord. Staining of additional end-stage G93A mutant SOD1 tissues showed specific upregulation of DP5/Hrk in lumbar spinal cord sections, but not in cerebellum or cortex. Finally, examination of protein expression using western blotting also revealed marked increases in DP5/Hrk and BNip3L in G93A mutant SOD1 lumbar spinal cord lysates compared to WT controls. The upregulation of a specific subset of BH3-only proteins, including Bid, DP5/Hrk, and BNip3L, in reactive astrocytes suggests that these proteins may execute a novel non-apoptotic function within astrocytes to promote ALS disease progression, thus providing a new potential target for therapeutic intervention.